Estimation of Stellate Ganglion Block Injection Point Using the Cricoid Cartilage as Landmark Through X-ray Review - Park, Jeong Soo (The Korean Pain Society, 2011)
BACKGROUND: Stellate ganglion block is usually performed at the transverse process of C6, because the vertebral artery is located anterior to the transverse process of C7. The purpose of this study is to estimate the location of the transverse process of C6 using the cricoid cartilage in the performance of stellate ganglion block. METHODS: We reviewed cervical lateral neutral-flexion-extension views of 48 patients who visited our pain clinic between January and June of 2010. We drew a horizontal line at the surface of the cricoid cartilage in the neutral and extension views of cervical lateral x-rays. We then measured the change in the shortest distance from this horizontal line to the lowest point of the transverse process of C6 between the neutral and extension views. RESULTS: There was a statistically significant difference in the shortest distance from the horizontal line at the surface of the cricoid cartilage to the lowest point of transverse process of C6 between neutral position and neck extension position in both males and females, and between males and females in both neutral position and neck extension position. The cricoid cartilage level was 4.8 mm lower in males and 14.4 mm higher in females than the lowest point of transverse process of C6 in neck extension position. CONCLUSIONS: Practitioners should recognize that the cricoid cartilage has cephalad movement in neck extension. In this way, the cricoid cartilage can be still useful as a landmark for stellate ganglion block.